Pengaruh FOMO (Fear Of Missing Out) Melalui Media Sosial Instagram Terhadap Sifat Impulsive Buying Mahasiswa STIE Surakarta - Ira Septiana; Satria Variansyah Wiguna (AKUNTANSI 45, 2025)
This investigation delves into the effects of Fear of Missing Out (FOMO) on social platforms like Instagram regarding spontaneous shopping habits among learners at STIE Surakarta. The FOMO concept emerges from intense online interactions, compelling people to chase current trends to maintain their social connections and avoid isolation. Our approach was quantitative, relying on firsthand information gathered from 102 engaged students via distributed surveys. We processed the data through assessments of validity and reliability, basic assumption checks, multiple linear regression analysis, t-tests, F-tests, and the R² coefficient, all supported by SPSS 25 tools. Key outcomes demonstrate that FOMO exerts a positive and meaningful influence on impulsive purchasing patterns. In the same vein, engagement with Instagram produces a positive and significant outcome. When combined, these elements yield a strong overall impact, as shown by an R² of 0.460, signifying that FOMO and Instagram account for 46% of the fluctuations in such behaviors. Ultimately, this evidence highlights that greater FOMO intensity and more frequent Instagram involvement correlate with a higher likelihood of students engaging in hasty, unprepared buying decisions.